The Therapeutic Effect of Traditional Chinese Medicine on Inflammatory Diseases Caused by Virus, Especially on Those Caused by COVID-19 - Li, Peng; Hu, Shuang; Qian, Cheng; Yao, Yan; Li, Liang-yun; Yang, Jun-fa; Yang, Li; Yang, Chen-chen; Zhou, Hong; Wang, Shu-xian; Hu, Ying; Zhu, Xing-yu; et al. (Frontiers in Pharmacology, 2021)
Inflammasomes are large multimolecular complexes best recognized for their ability to control activation of caspase-1, which in turn regulates the maturation of interleukin-1 β (IL-1β) and interleukin-18 (IL-18). IL-1β was originally identified as a pro-inflammatory cytokine able to induce both local and systemic inflammation and a febrile reaction in response to infection or injury. Excessive production of IL-1β is associated with autoimmune and inflammatory diseases. Both coronavirus disease 2019 (COVID-19) and severe acute respiratory syndrome (SARS) are characterized by an overexuberant inflammatory response and, for SARS, viral load is not correlated with the worsening of symptoms. However, there are no specific drugs are available for the treatment of this disease. As an important part of medical practice, TCM showed the obvious therapeutic effect of SARS-CoV infected patients. In this article, we summaries the current applications of TCM in the treatment of COVID-19 patients. Herein, we also provide an insight into the mechanism underlying the therapeutic effect of TCM, as well as novel naturally occurring compounds with anti-coronaviral activity are also introduced, in order to provide a new and potential drug development strategy for the treatment of COVID-19.